The Analysis of Iranian Students’ Persistence in Online Education - Mahmodi, Mahdi; Ebrahimzade, Issa (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
In the following research, the relationship between instructional interaction and student persistence in e-learning has been analyzed. In order to conduct a descriptive- analytic survey, 744 undergraduate e-students were selected by stratified random sampling method to examine not only the frequency and the methods of establishing an instructional interaction, but also the barriers to the student persistence in e-learning. The research findings confirmed the relationship between the instructors’ and the students’ application of two interaction methods including the discussion forum and email (asynchronous method), as well as the relationship between the frequency of instructional interaction and the student persistence in e-learning. According to the findings, family and job commitment, loss of instructional motivation and economic problems constitute the most important barriers to the student persistence in e-learning. The research results can help reduce one of the primary concerns of online learning, that is the student persistence rate, if they would be implemented in various instructional systems such as higher instructional system, for the purpose of providing favorable condition in e-learning, facilitating online learning interactions and, eventually, increasing the student persistence in e-learning.